Perspektif Manajemen “George Robert Terry” pada Corporate Social Responsibility (CSR) Di Kabupaten Wajo - Syam, Herdi; Najeminur, Najeminur; Patmasari, Eka; Abbas, Muh. Hasbi; Aris, Muhammad (Politeknik Bumi Akpelni, 2023)
Corporate Social Responsibility (CSR) is a program that synergizes corporate responsibility, the role of government, and how the community is the target of activities. This article results from research conducted in Wajo Regency, which started from the need for optimal CSR management related to planning and evaluation. The aim is to produce analytical material and stakeholder input to increase CSR management's effectiveness. The research method uses qualitative data collection techniques through observation, interviews, and literature analysis. Then, data processing is carried out using reduction techniques, and research results are displayed using descriptive sentences. Management of Corporate Social Responsibility (CSR) in Wajo Regency, if analyzed using George Robert Terry's management functions, found that the Regional Government has carried out or carried out management functions well, namely planning, organizing, implementing, and controlling. However, it is necessary to increase community empowerment in management functions.